2022
DOI: 10.1007/s00227-022-04111-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in adult size of green turtles at Aldabra Atoll and implications for clutch size, sexual dimorphism and growth rates

Abstract: Around the world, declines in the mean size of nesting sea turtles have been reported with concerns of a concomitant decrease in the reproductive output of populations. Here, we explore this possibility using long-term observations of green turtles (Chelonia mydas) at Aldabra Atoll, Seychelles. Based on > 4500 individual measurements over 21 years (1996–2016), we found the curved carapace length of nesting females declined by about 0.64 cm per decade, from 111.43 to 110.08 cm. For 391 individuals that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The approach used by Colman et al (2015) and Bellini et al (2019) was modified for this study by applying a small growth rate to fill the data gaps for larger immature/small mature turtles (67-109 cm CCL for green and 73-87 cm CCL for hawksbill turtles). Turtles in the smaller end of these ranges in other studies have been found to have spikes in growth (as discussed above), but then once sexual maturity is reached, annual growth appears to become very low (Omeyer et al 2017;Mortimer et al 2022). Coupled with the small sample size in this study of larger immatures/small mature turtles, this approach could be overestimating age and needs further investigation.…”
Section: Age At Sexual Maturitymentioning
confidence: 60%
See 3 more Smart Citations
“…The approach used by Colman et al (2015) and Bellini et al (2019) was modified for this study by applying a small growth rate to fill the data gaps for larger immature/small mature turtles (67-109 cm CCL for green and 73-87 cm CCL for hawksbill turtles). Turtles in the smaller end of these ranges in other studies have been found to have spikes in growth (as discussed above), but then once sexual maturity is reached, annual growth appears to become very low (Omeyer et al 2017;Mortimer et al 2022). Coupled with the small sample size in this study of larger immatures/small mature turtles, this approach could be overestimating age and needs further investigation.…”
Section: Age At Sexual Maturitymentioning
confidence: 60%
“…Published adult growth rates in peer-reviewed literature from nesters at Aldabra (for green turtles) and rookeries in the Seychelles (for hawksbill turtles) were used in the model to estimate age at sexual maturity. For green turtles, we used the mean nesting size (108.9 cm CCLn-t) from Aldabra collected during 1995-2016 (Mortimer et al 2022) and a female adult growth rate of 0.14 cm year −1 from Aldabra nesters (Mortimer et al 2022) in the model. For hawksbill turtles, we used the mean nesting size (86.4 cm CCLn-t) from Cousine Island, Seychelles (Gane et al 2020) and an adult growth rate of 0.17 cm year −1 for females > 80 cm CCL (Coral Sea, Queensland, Australia; Bell and Pike 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For green turtles, we used the mean nesting size (108.9 cm CCLn-t) on Aldabra from 1995-2016 (n = 4635; SIF unpubl. data, same dataset from Mortimer et al 2022, and a female adult growth rate of 0.14 cm year-1 from Aldabra nesters (Mortimer et al 2022) in the model. For hawksbill turtles, we used the mean nesting size (86.4 cm CCLn-t) from Cousine Island, Seychelles (Gane et al 2020), and an adult growth rate of 0.17 cm year-1 for females > 80 cm CCL (Coral Sea, Queensland, Australia; Bell and Pike 2012).…”
Section: Discussionmentioning
confidence: 99%